Separation of aligning and leveling stages to control mandibular incisor inclination: A randomized clinical trial - Pornpat THEERASOPON; Steven J. LINDAUER; Chairat CHAROEMRATROTE (Dental Press Editora, 2021)
ABSTRACT Objective: To determine whether separating the alignment and leveling phases can reduce proclination of the mandibular incisors. Methods: Eligibility criteria included Class I subjects with an irregularity index of 3-5 mm, 3-4 mm curve-of-Spee (COS), and non-extraction treatment. Thirty adults were randomly allocated into two groups: (1) Control group was leveled and aligned simultaneously with flat archwires progressively to 0.016x0.022-in stainless-steel; (2) Experimental group was aligned first with 0.014-in-superelastic NiTi with mild accentuated COS, then leveled using 0.016x0.022-in beta-titanium accentuated COS archwires and gradually reduced the curve until flat. Mandibular incisor position and inclination were evaluated by cephalometric analysis. COS and irregularity index were evaluated in study models. Assessment was conducted twice after 0.016-in NiTi and after 0.016x0.022-in stainless-steel archwire placements. Dental changes from cephalograms and models were compared within group using paired t-test and between groups using independent t-test. Results: Control group: Round-wire-phase, mandibular incisors tipped labially (4.38° and 1 mm) with intrusion (-1.13 mm); Rectangular-wire-phase, mandibular incisors further intruded and proclined (-0.63 mm and 1.38°). Experimental group: During aligning with round accentuated COS archwires, mandibular incisors tipped very slightly labially (0.75° and 0.50 mm) with no significant intrusion; during leveling with rectangular archwires, incisors majorly intruded (1.75 mm) with slight proclination (1.81°). The experimental group had significant less incisor proclination (control: 5.76°, experimental: 2.56°) with more incisor intrusion (control: -1.75 mm, experimental: -2.13 mm). The COS in experimental group showed significant greater reduction (-2.88 mm) than that of the control group (-1.69 mm). Conclusion: In control group, mandibular incisor proclination was markedly observed in round archwires, with further proclination caused by rectangular archwires. In experimental group, minimal proclination was exhibited when accentuated COS round archwires were used for aligning. Leveling with rectangular archwires caused less proclination with more COS reduction.